LncRNA MEG3 Protects Chondrocytes From IL-1β-Induced Inflammation via Regulating miR-9-5p/KLF4 Axis - Huang, Yijiang; Chen, Daosen; Yan, Zijian; Zhan, Jingdi; Xue, Xinghe; Pan, Xiaoyun; Yu, Huachen (Frontiers in Physiology, 2021)
Background: Osteoarthritis (OA) is a chronic disease of degenerative joints characterized by articular cartilage damage, subchondral bone remodeling, osteophyte formation and inflammatory changes. Chondrocyte apoptosis is definitely linked to cartilage degeneration. This work aimed to investigate the protective role of long non-coding RNA (lncRNA) maternally expressed 3 (MEG3) against the apoptosis of chondrocytes. Methods: Chondrocyte cell lines, CHON-001 and ATDC5 were treated with different doses of interleukin-1β (IL-1β), to mimic the inflammatory response during OA pathogenesis; qRT-PCR was exerted to measure MEG3, miR-9-5p and Krüppel-like factor 4 (KLF4) mRNA expressions; MEG3 overexpression plasmids, MEG3 shRNA, miR-9-5p mimics, miR-9-5p inhibitors and KLF4 overexpression plasmids were transfected into the cells; CCK-8, wound healing assay and flow cytometry were conducted to determine the cell viability, migration and the apoptotic rate; dual-luciferase reporter assay was used to validate the targeting relationships among MEG3, miR-9-5p, and KLF4. Western blot was used to detect KLF4 protein expression; ELISA assay was employed to measure the contents of inflammatory factors. Results: MEG3 expression in chondrocytes was down-regulated by the stimulation of IL-1β, and MEG3 negatively regulated miR-9-5p expression, but positively regulated KLF4 expression. MEG3 overexpression strengthened the viability and migration of CHON-001 and ATDC5 cells, while restrained their apoptosis and inflammatory response, while MEG3 knockdown had opposite effects; miR-9-5p inhibition or KLF4 overexpression could counteract the effect of MEG3 knockdown on chondrocytes; MEG3 was proved to be a molecular sponge for miR-9-5p, and KLF4 was validated as the target of miR-9-5p. Conclusion: MEG3 can protect CHON-001 and ATDC5 from IL-1β induced injury via repressing miR-9-5p and up-regulating. This work suggest that MEG3 can probably be a protective factor during the pathogenesis of OA by increasing the viability of chondrocytes.